ANALISIS KELAYAKAN FINANSIAL USAHATANI BELIMBING MANIS DI KECAMATAN MINAS KABUPATEN SIAK PROVINSI RIAU - Desi Guinanda; Khairizal (UIR Press, 2023)
Sweet star fruit is one of the horticultural plants that are rich in benefits and are often consumed by the community as a fulfillment of vitamin needs and as a medicine for hypertension. Minas District is one of the star fruit-producing areas in Siak Regency, Riau Province. With demand and production that tend to increase, sweet star fruit farming has prospects for development. This study aims to analyze the financial feasibility of sweet star fruit farming. The method used in this study is a survey method and was conducted in Minas District, Siak Regency, Riau Province. This study was conducted for 6 months, starting from December 2021 to May 2022. A total of 10 sanples was purposively selected from 35 population with the consideration that the samples have more than 100-star fruit trees. The data used in this study consisted of primary and secondary data. The type of data used was quantitative and qualitative descriptive data. The results showed that sweet star fruit farming was feasible financially to be run and developed because the investment criteria with an NPV value of IDR 517,921,323 > 0, Net B/C 1.96 > 1, IRR 16% > the applicable interest rate in this study is 6%, and with PP of 8 years 5 months 7 days from the business projection.